Co-occurrence of Attention-Deficit/Hyperactivity Disorder in participants with Autism Spectrum Disorder in a Centre for Neurodevelopment and Autism in Children, Bangladesh - Mahmuda Akhter; Muhammad Jabed Bin Amin Chowdhury; Mohammad Nur Alam Din; Mursheda Khanom; Aditi Chowdhury; Mohammad Toufiqul Islam; Bithi Debnath (Bangladesh Critical Care Journal, 2025)
Background: The relationship between Autism spectrum disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD), and in particular the prevalence of ADHD among the ASD population in our setting is scarcely studied. Aims: The study aimed to determine the frequency of ADHD in a sample of Bangladeshi children and adolescents with ASD. Materials and Methods: This study was conducted at Centre for Neurodevelopment and Autism in Children (CNAC), BMU, Dhaka, Bangladesh. One hundred children having the diagnosis of ASD were included in the study. ADHD signs and symptoms were established by interview and questionnaire by center’s experts. ADHD symptoms were based on the individuals’ behaviors that was present after the benefits of medications wore off or during drug holidays. Results: The mean age of the studied children was 7.77 (±5.811) years and age ranged from 2 to 17 years, 75% were male, and most of the children were from middle and upper-middle class family (71.0%)]. The rate of clinically evaluated ADHD symptoms in ASD was 17% (95% confidence interval: 10.23%-25.82%).‘Often has difficulty sustaining attention in tasks or play activities’ and ‘Often avoids, dislikes, or is reluctant to engage in tasks that require sustained mental effort’ were the most (14.0%) found complaints of ADHD in children with ASD; followed by, ‘Often fails to give close attention to details or makes careless mistakes in schoolwork, work or other activities’ (13.0%) and ‘Often has difficulty organizing tasks and activities’ (12.0%). Conclusion: Two out of every 10 children with ASD have ADHD. Bangladesh Crit Care J March 2025; 13 (1): 35-38